Improving IEEE 802.11g Mac to Support Quality of Service for Multimedia Applications in Wireless Networks - Md Khambari, M. N.; Sahib, S.; Othman, M. F. I. (2009)
This paper paper investigates, describes and propose better techniques to provide QoS by assigning new metrics to the DCF access method, involving the DCF Interframe Space (DIFS), Contention Window values and the maximum data packet size to high priority nodes, which will bias towards high priority multimedia traffic to support QoS. A simulation is done using Network Simulator 2 (NS-2) and comparisons were made between different sets of network simulation scenarios. Improvements on throughput, delay and jitter can clearly be seen and further analysis is then presented.